Visual and Auditory Cue Effects on Risk Assessment in a Highway Training Simulation. (October 2013) - Toet, Alexander; Houtkamp, Joske M.; van der Meulen, Ralph
We investigated whether manipulation of visual and auditory depth and speed cues can affect a user's sense of risk for a low-cost nonimmersive virtual environment (VE) representing a highway environment with traffic incidents. The VE is currently used in an examination program to assess procedural knowledge of highway patrol officers. In its original form, the VE did not convey the danger of the simulated incidents, and trainees did not experience a sense of risk, even though important elements which contribute to a sense of danger in reality (like the speed and proximity of vehicles) were accurately modeled. This deficiency seriously degrades the validity of the VE as an examination tool. To provide viewers a more compelling impression of a simulated highway incident, we added variability to traffic behavior, and enhanced and added several visual and auditory depth and speed cues in the VE, which are known to affect risk perception in reality. Participants passively watched video clips of both the original and the enhanced versions of the simulation, and actively performed a lane crossing task in both interactive versions of the VE. Then, they filled out questionnaires addressing their speed, distance, and risk perception. The implemented changes did not affect speed and distance estimates, but significantly increased perceived personal risk. These results show that relatively minor changes to the visual, auditory, and dynamic aspects of a VE, established through proper analysis of user requirements and tasks, can significantly influence a user's experience, and thus determine the validity of the simulation for training and evaluation applications.